The Development of Problem-Based Learning Activities to Promote Science Process Skills of Grade 1 Students - Phothisa, Bandit; Worakham, Paisarn (Journal of Education Rajabhat Maha Sarakham University, 2024)
The objectives of this research were: 1) to compare learning achievement with the 80 percent criteria and 2) to study science process skills. The research instruments were: 1) 6 problem-based learning management plans, 2) 30 items of three multiple-choices achievement test and 3) 30 items of subjective test on science process skill. The data analysis statistics included mean, standard deviation, percentage and dependent sample t-test. The results of the study on development of problem-based learning activities to promote science process skills of grade 1 students were as follows: 1) Learning achievement of the grade 1 students who learned with problem-based learning management on “Things Around Us” was higher than the 80 percent criteria at statistically significant of .05 level and 2) Grade 1 students who learned with problem-based learning on “Things Around Us” had increased basic science process skills including observation skills, inferring skill and classifying skill.